Housing First and the reduction of homelessness in Finland among people with substance abuse problems - Karhula, Aleksi; Ollonqvist, Joonas; Leni, Elisabetta; Niemi, Veera; Moisio, Pasi (Edward Elgar Publishing, 2026)
Finland's response to homelessness is based on Housing First, a comprehensive approach that combines unconditional access to housing, tailored support, and homelessness prevention. The Finnish studies have relied on mixed-methods data, but the use of national level register data has been quite narrow. We analyze the implementation of Housing First programs (PAAVO I, PAAVO II, and AUNE) and their temporal correlations with the number of homeless people with substance use problems, their likelihood of being alive two years after the treatment period, and their housing situation two years after the treatment period. Homeless people with substance use problems are identified from the national registers based on their visits to substance use treatment services. Our results show that the number of homeless people with substance abuse problems has declined during the time of Housing First programs (2008–2017), there has been very little change in their mortality, but a larger share had permanent housing two years after the treatment period.
Beyond the Nordic Welfare State. Extending Social Investments with Interventions.